THE PUBLIC INSTRUCTION PROCESS 90 YEARS OF THE “SEVEN TESTS” OF JOSÉ CARLOS MARIÁTEGUI - Arroyo Laguna, Eduardo (2020)
The Spanish inheritance has not only been a method of instruction, of education butcentrally an economic and social regime. Education and teaching must be seen aseconomic and social problems. The French influence was inserted, later, in this contextwith the complacency of those who saw in France the homeland of Jacobin and republicanfreedom as those who at the same time and at the same time were inspired by thethought and practice of conservative restoration . The American influence prevails in theend, although with setbacks, as a result of a country that started an embryonic capitalistdevelopment at the same time that it imported American capital, ideas and technicians.The aim is to explain how Peruvian public education has managed to break into Peruviansociety, but at the same time how it also implies its failure in the 21st century.